Essentials of construction project management - Uher, Thomas E. (Construction management (Sydney, N.S.W.), 2004)
This book has been written as a text and reference for project management courses in both undergraduate and postgraduate building construction management courses, and quantity surveying, architecture and civil engineering programs. Its focus is on the application of important issues of project management in the construction industry. --